GROUNDWATER QUALITY IN SHALLOW WELLS FROM FELEACU VILLAGE, CLUJ COUNTY, ROMANIA - BURCĂ, Silvia; INDOLEAN, Cerasella; MĂICĂNEANU, Andrada (Studia Universitatis Babeș-Bolyai Chemia, 2015)
This study includes monitoring one of the most important physico-chemical parameters in ten shallow wells from Feleacu village, Cluj County, Romania, in order to establish if the water sources can be used as drinking water. dHt, dHT, COD, TDS, conductivity, pH, NO2-, NH4+, Mn2+ and Fetotal were determined using appropriate standard methods and compared with allowable values for drinking water, according to Romanian legislation. Based on the determined parameter values, most of the samples were characterized by high mineralization and some of them are contaminated with nitrite ions. Thus, in order to ensure that the water consumed as drinking water will not create health problems for the population, periodically monitoring of physico-chemical parameters should be compulsory performed.